Arrow. The complete second season [videorecording (DVD)]. - Blackthorne, Paul; Holland, Willa, 1991-; Ramsey, David; Thompson, Susanna, 1958- (Warner Brothers Home Entertainment, 2014)
Starling City has been torn apart by the Undertaking, so the need for the hooded vigilante, now known as The Arrow, is more urgent than ever in the explosive second season of the hit action series based on DC Comics' Green Arrow. After retreating to the island on which he was once stranded Oliver Queen returns to protect his mother, sister and besieged company, but comes to realize that allies and enemies have switched sides, and the stranglehold of evil on family, friends.